Precision indoor positioning with ultra-wideband (UWB) technology - Mohd Sultan, Juwita; Kamaruzaman, Nurul Najihah; Md Yusop, Azdiana; Manap, Zahariah; Chaudhary, Amir Rashid; Mohd Ali, Darmawaty (Wydawnictwo SIGMA-NOT, 2024)
Ultra- Wideband (UWB) is a radio-based communication technology that allows for quick and reliable data transmission over short distances. This paper explores the application of UWB in indoor localization systems tailored for emergency response operations. A persistent challenge during emergency rescues is the loss of communication and tracking capabilities for responders within a building, making it impossible for those outside to pinpoint their exact locations. The aspiration of this project is to develop a device that could track the indoor location using a microcontroller and the DWM 1000. This system will be designed to track and collect data from on-scene situations such as collapsed buildings, landslides, and other natural disasters. On exact measurements of the transmitted time of arrival (ToA) and time difference of arrival (TDoA), the system is built. While TDoA merely deals with relative time for all receivers, ToA requires accurate knowledge of the synchronizing and transmitting times between the transmitter and receiver. Aside from that, measurements will be used to evaluate the performance of the DWM 1000 UWB parameters. Beyond its utility in emergency response, the system empowers precise control and localization of first responders using UWB technology, providing fast, accurate, real-time object tracking and tracing for indoor applications. The system's versatility extends to assisting visually impaired individuals in navigating unfamiliar spaces, aiding in emergency evacuations in smoke-filled environments, and enhancing child safety in crowded venues.